DECISION-MAKING PECULIARITIES OF SOCIAL WORKERS IN SOCIAL CARE INSTITUTIONS - Urniežienė, Daiva; Garšvė, Lina (PROFESSIONAL STUDIES: Theory And Practice, 2024)
The peculiarities of decision-making by social workers in social care institutions are analyzed in the article. It introduces how social workers cope with delicate and socially sensitive situations according to the clients, of social care institutions, welfare. Ethical commitments and empathy of social workers, personal indications of client’s needs and objectives, are emphasized in the research. When a social worker is a team member and collaborates with other specialists, the interdisciplinary aspect of decision-making is indicated in the article.